1964
DOI: 10.1259/0007-1285-37-442-775
|View full text |Cite
|
Sign up to set email alerts
|

Radiology in Acute Abdominal Disorders due to Meckel's Diverticulum

Abstract: Forty-two cases with a Meckel's diverticulum causing acute abdominal symptoms were examined radiologically and are reported. X-ray examination of the abdomen may help to establish the diagnosis by showing peritoneal irritation, pneumoperitoneum, calcification in the diverticulum or oedematous ileal loops. Inflammation in the Meckel's diverticulum, contrary to appendicitis, seems very rarely to produce gas and a fluid level in the caecum. In small children, with a low obstruction, Meckel's diverticulum is in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1968
1968
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Similar findings were reported in a study by Enge and Frimann-Dahl (12) in which 80% of patients with symptomatic diverticula had abnormal roentgen findings, although barium filled the diverticulum in only 4%. The prevailing attitude of pessimism in regard to the role of radiology in this entity is not well-founded, as the secondary effects of the diverticulum are often seen and may provide useful information to the clinician despite the lack of a definite diagnosis.…”
Section: Roentgen Findingssupporting
confidence: 90%
“…Similar findings were reported in a study by Enge and Frimann-Dahl (12) in which 80% of patients with symptomatic diverticula had abnormal roentgen findings, although barium filled the diverticulum in only 4%. The prevailing attitude of pessimism in regard to the role of radiology in this entity is not well-founded, as the secondary effects of the diverticulum are often seen and may provide useful information to the clinician despite the lack of a definite diagnosis.…”
Section: Roentgen Findingssupporting
confidence: 90%
“…In patients presenting with bleeding due to Meckel's diverticulum, there is usually no pathology in endoscopic evaluation. Because of this, other imaging methods such as CT Angiography and scintigraphy are referred (Enge and Frimann-Dahl, 1964). Duodenal ulcer was detected in our patient, which could explain the bleeding.…”
Section: Discussionmentioning
confidence: 70%
“…Enge and Frimman-Dahl (5) found that 80 per cent of patients with symptomatic diverticula had abnormal Xray findings, but these were mainly plain film changes related to the complications, only 2 of the 42 patients having barium demonstration of the diverticulum. The plain film changes showed signs of obstruction, intussusception, ileus and perforation.…”
Section: Plain Film Examinationmentioning
confidence: 98%
“…MECKEL ( I ) described this diverticulum in 1809. It was demonstrated radiologically in 1926 (2), and the first radiological investigation was undertaken by Phaler (3)(4)(5). This report describes the radiological demonstration of 3 patients.…”
mentioning
confidence: 89%